Investigation of initial metallurgical factors on the dynamic impact response and adiabatic shear bands formation of the 6061 Al alloy - Singh R.K.; Guraja S.S.S.; Ajide O.O.; Owolabi G.M.; Kumar N. (My University, 2025)
The effect of multi-pass friction stir processing and initial base metal condition on the dynamic impact response of AA6061-T6 alloy at high strain rates was investigated in this study. The Split-Hopkinson Pressure Bar (SHPB) was used in dynamic experiments with strain rates ranging from 1600 to 4200/s. The results revealed that the base metal alloy's (BM) dynamic flow stress was comparable to all the friction stir processed AA6061-T6 (FSP'd) specimens as the strain rate and true strain increased. The general increase in stress response levels as strain rates and true strain increases can be attributed to strain hardening. The higher values of strain rate sensitivity in multi-pass FSP'd specimens are an indication that they are more ductile in comparison to the BM condition. The optical and electron backscattered diffraction (EBSD) analysis showed that adiabatic shear bands were formed by heterogeneous deformation. The EBSD analysis revealed that the FSP'd specimens showed more abnormal grain growth and dynamic recrystallized sites than BM. The substantial decrease in dynamic flow stress, and high strain rate sensitive values of multi-pass FSP'd specimens compared to BM for all the investigated strain rates attributed to softening effect by dynamic recrystallization (DRX), and the emergence of abnormal grain growth during friction stir process. © 2023 Elsevier B.V.